6‐Methylenebicyclo[3.2.1]oct‐1‐en‐3‐one: A Twisted Olefin as Diels–Alder Dienophile for Expedited Syntheses of Four Kaurane Diterpenoids. (17th September 2019) - Wang, Junjie; Ma, Dawei
Abstract: 6‐Methylenebicyclo[3.2.1]oct‐1‐en‐3‐one, a twisted and highly reactive enone, was prepared for the first time by elimination of its bromide precursor. Its reactions as a dienophile with several dienes in Diels–Alder reactions proceeded smoothly to provide tricyclic and tetracyclic adducts, which allowed short syntheses (10–11 steps) of four kurane diterpenoids including 11β‐hydroxy‐16‐kaurene, 11α‐hydroxy‐16‐kaurene, liangshanin G, and gesneroidin B. Abstract : Mit einem Twist : 6‐Methylenbicyclo[3.2.1]oct‐1‐en‐3‐on, ein verdrehtes und hochreaktives Enon, wurde durch Eliminierung seiner Bromidvorstufe hergestellt. Es reagiert bereitwillig als Dienophil mit mehreren Dienen in Diels‐Alder‐Reaktionen und liefert tri‐ und tetracyclische Addukte, die kurze Synthesen (10–11 Schritte) von vier Kuran‐Diterpenoiden ermöglichen, darunter 11β‐Hydroxy‐16‐kauren, 11α‐Hydroxy‐16‐kauren, Liangshanin G und Gesneroidin B.